This Study Efektivitas Sistem Pembelajaran Jarak Jauh Di Madrasah Ibtidaiyah Modern Miftahul Ulum Bogor - Nur Utami, Annisa; Zahruddin, Zahruddin (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
This study aims to determine the level of effectiveness of distance learning at Madrasah Ibtidaiyah Modern Miftahul Ulum which has been implemented since government policies were issued during the Covid-19 pandemic, which is from March 2020 – December 2020. The method used uses a qualitative descriptive method. The data collection technique uses direct observation where the author is a teacher at the madrasa, interviews through the google page form given to teachers and students' guardians, and study of document completeness of the file. The results show that the distance learning system in this madrasa has low effectiveness because there are still several obstacles in carrying out activities such as the unavailability of gadget facilities and quotas, minimal initial abilities of students such as not being fluent in reading and writing, the time that parents have in accompanying them. children learn. In addition, in terms of the evaluation results, there are still many participants who take remedial, this shows that students have not succeeded in achieving the expected competencies.